Message transmisson model in dense graphs for ad hoc networks - 394003 Sakhinah Abu Bakar; Shaharuddin Salleh; Annual Fundamental Science Seminar (2004 : Universiti Teknologi Malaysia, Skudai) (Skudai : Universiti Teknologi Malaysia, 2004)
13